2017
DOI: 10.3415/vcot-16-09-0127
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and complications of thoracic and pelvic limb stump and socket prostheses

Abstract: Stump socket prostheses are feasible and versatile in animals. In correctly selected cases, good to excellent outcomes are possible. However, complications are frequent but often manageable. Further investigations are required into the risk factors for poor outcomes and prospective studies are required to assess changes in biomechanics, function, and QOL before and after fitting of a stump socket prosthesis. Until further evidence is available, careful consideration should be given before fitting bilateral tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…Additionally, most owners surveyed would elect to choose this treatment option again, and would recommend the use of socket prosthetics to another dog owner. Clinical outcomes in the present study appeared slightly better than previously reported outcomes (21). However, criteria utilized to determine clinical outcome differed between studies, therefore, direct comparison of these outcome scores cannot be made.…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…Additionally, most owners surveyed would elect to choose this treatment option again, and would recommend the use of socket prosthetics to another dog owner. Clinical outcomes in the present study appeared slightly better than previously reported outcomes (21). However, criteria utilized to determine clinical outcome differed between studies, therefore, direct comparison of these outcome scores cannot be made.…”
Section: Discussioncontrasting
confidence: 81%
“…Specific outcomes for these dogs were not reported. Another study reported on three patients with an antebrachial defect and three patients with defects at the tarsocrural joint or proximal (21). Outcomes of 2/3 dogs with antebrachial defects were defined as good, 1/3 was poor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations